The Learning Science with Digital Pop-Up Book Media - Sri Rahmayanti; Topan Setiawan (Postgraduate, University of Mataram, 2023)
The era of society 5.0 requires the use of digital technology to be stronger. In this study, it will be seen how the implementation of the use of digital technology in the field of education. The purpose of this study is to determine the design form and efforts to develop Pop-Up Book learning media as learning media.Â This research method uses the Research and Development (R&D) research type. Research and development (R&D) is a process or method used to validate and develop a product. The results of research on the development of Pop-Up Book Learning Media can improve students' critical thinking skills. Teachers have designed lesson plans, but when viewed from the perspective of learning media, a learning media is needed that is packaged in an interesting and comprehensible manner so as to increase interest in student participation in learning, and also to increase student criticality. Therefore, researchers will develop Pop-Up Book learning media to improve students' critical thinking skills. From the problems that have occurred and from previous research as support, an effort is needed to help solve the problems that occur by developing media that can attract interest and increase student understanding. The development of Pop-Up Book Learning Media to Improve Students' Critical Thinking Skills can be carried out by steps: preliminary studies, preparation of initial product drafts, determining basic competencies, designing Pop-Up Book learning media drafts, designing lesson plans, utilizing selected media, involving students in learning by using media and conducting evaluations and revisions.